An automated shopping trolley / Mikhael Imran Mohd Shukri - Mohd Shukri, Mikhael Imran (2024)
Despite significant advancements in modern technology, shopping cart design and innovation have remained unchanged. Manually pushing the shopping trolleys lead to collision and inconveniences. In addition, the security and human are at risk for shopping during the nighttime as well as they may lead to overspending without proper grocery management plan. This thesis presents an automated follow me trolley utilizing the Bluetooth, ultrasonic, counting system, and smart lighting system. The ultrasonic sensor utilizes in the following system and anti-collision system. The design was verified by using simulation via proteus software that show the LED turn on during the low-light intensity. Additionally, the motor worked well with the ultrasonic sensors' reactions. Despite the suggested arrangement, a further improvement can be built by including some features, such as a cashier-less system, to ensure sustainability and better labour costs